Relocations reading culture in South Africa - Coovadia, Imraan 1970-; Parsons, Cóilín; Dodd, Alexandra ca. 20./21.Jh (UCT Press, 2015)
"[E]ssays by world-renowned as well as emerging writers, artists and thinkers ... The essays, which began their lives as part of the Great Texts/Big Questions lecture series at the University of Cape Town, cover a wide range of subjects ... These imaginative explorations all engage in meaningful and often unusual ways with the current landscape of South African culture and creative thinking, reflecting on culture in the wake of decolonisation and asking questions about the place of the arts and humanities in a postcolonial world."--Back cover